2022
DOI: 10.18502/jabs.v11i2.8781
|View full text |Cite
|
Sign up to set email alerts
|

Association of High Levels of Testosterone and Ferritin with Overweight in Women with PCOS

Abstract: Background & Objective: The present study was conducted to determine testosterone and ferritin levels in women with polycystic ovary syndrome (PCOS) and investigate its relationship with body mass index (BMI) Materials & Methods: In this case-control study, 104 PCOS cases and 99 controls were included. The concentration of testosterone, ferritin, lipid profile, insulin, glucose, and androgen was measured in fasting blood samples. Results: Testosterone level was equal to 1.08 ± 0.50 and 0.85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…This study found that serum ferritin concentration did not appear to change in women with PCOS. Our results were incompatible with Barartabar et al (1) who revealed that ferritin levels in serum were elevated in PCOS women and PCOS women with obesity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This study found that serum ferritin concentration did not appear to change in women with PCOS. Our results were incompatible with Barartabar et al (1) who revealed that ferritin levels in serum were elevated in PCOS women and PCOS women with obesity.…”
Section: Discussioncontrasting
confidence: 99%
“…The most communal endocrinopathy in females of reproductive age (15-44 years) is Polycystic ovary syndrome (PCOS), with an incidence of 5-10% (1). Polycystic ovary syndrome influences numerous systems and have several complications like irregular menses, infertility, insulin resistance, acanthosis nigricans, hir¬sutism, and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Testosterone levels in the current research were elevated significantly (P<0.05) in the PCOS group compared to the control group, and this rise may be due to obesity, particularly abdominal obesity, and insulin resistance, which are linked to elevated blood testosterone levels. As a result of increased androgen and insulin resistance in PCOS patients, testosterone production in the ovaries rises [35]. Also, this increase mostly results from the inherent alteration of ovarian theca cells, characterized by a disruption in the expression and/or activity of essential steroidogenic enzymes [36].…”
Section: Discussionmentioning
confidence: 99%